Odpowiedzi

2010-02-09T21:41:31+01:00
Znajdź pierwiastki podanych trójmianów:
a) y = x² - 3x - 4 = 0
Δ = (-3)² -4*1*(-4) = 9 + 16 = 25
√Δ = √25 = 5
x1 = ( 3 -5): 2*1 = (-2) : 2 = -1
x2 = (3 + 5) : 2*1 = 8 : 2 = 4

b) y = -2x² + 2x + 24 = 0 /:(-2)
x² -x - 12 = 0
Δ = (-1)² - 4*1*(-12) = 1 + 48 = 49
√Δ = √ 49 = 7
x1 = ( 1 -7) : 2*1 = (-6) :2 = -3
x2 = ( 1 + 7) :2*1 = 8 : 2 = 4

c) y = -8x² - 52x - 60
-8x² - 52x - 60 = 0 ?:(-4)
2x² + 13x + 15 = 0
Δ = 13² -4*2*15= 169 - 120 = 49
√Δ=√49 = 7
x1 = (-13- 7): 2*2 = (-20) : 4 = -5
x2 = (-13 +7) : 2*2 = (-6) : 4 = - 6/4 = - 3/2

d) y = -2√2x² + 9x - 3√3
-2√2x² + 9x - 3√3 = 0

a = -2√2
b = 9
c = -3√3
Δ = 9² - 4*(-2√2)*(-3√3) = 81 - 24*√6
trudno obliczyć √Δ, gdzieś musi być bład w zadaniu

e) y = -(5x - 1)² - (9 - 2x)² + 3x + 82
-(5x - 1)² - (9 - 2x)² + 3x + 82 = 0
-(25x² -10x +1) -(81 - 36x + 4x²) + 3x + 82 = 0
-25x² + 10x -1 -81 +36x -4x² + 3x + 82 = 0
-19x² + 49x -82 + 82 = 0
-19x² + 49 x = 0
- x( 19x - 49) = 0
-x = 0 lub 19x - 49 = 0
x = 0 lub 19x = 49
x= 0 lub x = 49/19
Najlepsza Odpowiedź!
2010-02-09T23:11:00+01:00
A) y = x² - 3x - 4
Δ=b²-4ac
Δ=-3²-4×1×-4
Δ=9+16
Δ=25
x₁=-b-√Δ /2a
x₂=-b+√Δ /2a
x₁=3-5 /2
x₂=3+5 /2
x₁=-1
x₂=4

b) y = -2x² + 2x + 24
Δ=b²-4ac
Δ=2²-4×-2×24
Δ=4+192
Δ=196
x₁=-b-√Δ /2a
x₂=-b+√Δ /2a
x₁=-2-14 /-4
x₂=-2+14 /-4
x₁=4
x₂=-3

c) y = -8x² - 52x - 60
Δ=b²-4ac
Δ=-52²-4×-8×-60
Δ=2704-1920
Δ=784
x₁=-b-√Δ /2a
x₂=-b+√Δ /2a
x₁=52-28 /-16
x₂=52+28 /-16
x₁=-1,5
x₂=-5

d) y = -2√2x² + 9x - 3√3
Δ=b²-4ac
Δ=9²-4×-√8×-√27
Δ=81-4√216
Δ=22,2 (w przybliżeniu)
x₁=-b-√Δ /2a
x₂=-b+√Δ /2a
x₁=-9-4,7 /5,7
x₂=-9+4,7 /5,7
x₁=-2,4
x₂=-0,75

e) y = -(5x - 1)² - (9 - 2x)² + 3x + 82
y = -(25x²-10x+1) - (4x²-36x+81) + 3x + 82
y = -25x²+10x-1-4x²+36x-81+3x+82
y = -29x²+49x
Δ=b²-4ac
Δ=49²-4×-29×0
Δ=2401-0
Δ=2401
x₁=-b-√Δ /2a
x₂=-b+√Δ /2a
x₁=-49-49 /-58
x₂=-49+49 /-58
x₁=-1,5
x₂=1,7

http://www.fizykon.org/wzory/wzory_matem_trojmian_kwadratowy.htm
1 5 1